Public policy towards protected agriculture in the López Obrador government - Hernández Suárez, José Luis (Revista Mexicana de Ciencias Agrícolas, 2021)
During the Vicente Fox Quesada government, a public policy oriented to the development of protected agriculture was implemented, within the framework of the strategy to increase the competitiveness of the agricultural sector, which is a source of foreign exchange, and to complement the north American and Canadian economies in the supply of vegetables and ornamental plants. The area, the number of structures and production grew thereafter, but in the Andrés Manuel López Obrador government, business agricultural producers lost power to direct policy to the benefit of their interests as a result of changes in the correlation of forces. The objective of this paper was to analyze how this policy was terminated during 2020, based on a critical perspective of the conflict between social groups to advance their affairs and block the projects of their rivals. The study is based on texts on production and information on the positions of producers’ associations and the government. The results are a completion of supports for the production and commercialization of protected agriculture.